2022
DOI: 10.3390/s22218173
|View full text |Cite
|
Sign up to set email alerts
|

Assessment Tasks and Virtual Exergames for Remote Monitoring of Parkinson’s Disease: An Integrated Approach Based on Azure Kinect

Abstract: Motor impairments are among the most relevant, evident, and disabling symptoms of Parkinson’s disease that adversely affect quality of life, resulting in limited autonomy, independence, and safety. Recent studies have demonstrated the benefits of physiotherapy and rehabilitation programs specifically targeted to the needs of Parkinsonian patients in supporting drug treatments and improving motor control and coordination. However, due to the expected increase in patients in the coming years, traditional rehabil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 85 publications
0
14
0
Order By: Relevance
“…This novelty intends to overcome the limitations of many eHealth platforms and services that focus only on specific individual aspects without providing a comprehensive overview of the patient’s condition. Instead, this novelty could be particularly relevant from a clinical perspective, especially in complex and multi-system pathologies such as those considered by the REHOME project; The use of recent, innovative, and promising methodologies in the context of motor and cognitive rehabilitation, such as gamification and exergaming in virtual environments, to favor patient condition assessment and motor–cognitive training in playful, fun, life-situation-inspired, and rewarding environments, with a focus on patients’ engagement, needs, motivations, and aesthetic preferences [ 101 , 102 ]. This novelty intends to foster greater patient involvement and satisfaction, thus enticing the patient to continue with the treatment according to the therapeutic plan.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This novelty intends to overcome the limitations of many eHealth platforms and services that focus only on specific individual aspects without providing a comprehensive overview of the patient’s condition. Instead, this novelty could be particularly relevant from a clinical perspective, especially in complex and multi-system pathologies such as those considered by the REHOME project; The use of recent, innovative, and promising methodologies in the context of motor and cognitive rehabilitation, such as gamification and exergaming in virtual environments, to favor patient condition assessment and motor–cognitive training in playful, fun, life-situation-inspired, and rewarding environments, with a focus on patients’ engagement, needs, motivations, and aesthetic preferences [ 101 , 102 ]. This novelty intends to foster greater patient involvement and satisfaction, thus enticing the patient to continue with the treatment according to the therapeutic plan.…”
Section: Discussionmentioning
confidence: 99%
“…The use of recent, innovative, and promising methodologies in the context of motor and cognitive rehabilitation, such as gamification and exergaming in virtual environments, to favor patient condition assessment and motor–cognitive training in playful, fun, life-situation-inspired, and rewarding environments, with a focus on patients’ engagement, needs, motivations, and aesthetic preferences [ 101 , 102 ]. This novelty intends to foster greater patient involvement and satisfaction, thus enticing the patient to continue with the treatment according to the therapeutic plan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a randomized controlled trial, Stillerova et al reported that monitoring PD symptoms using videoconferencing may be useful to give an overall idea of symptom severity over time [ 53 ]. In a randomized crossover pilot study of telemedicine, Sekimoto et al demonstrated that the outcomes of telemedicine were comparable to those of face-to-face visits, though the authors revealed some limits, such as evaluations that require in-person contact (such as rigidity and postural stability measures) [ 49 , 55 ]. Motor rehabilitation via telemedicine has also demonstrated its efficacy if conducted at home [ 56 ].…”
Section: Methodsmentioning
confidence: 99%
“…tDCS’s portability, high acceptability, and user-friendly interface make it an easy application for telemedicine practices. Dobbs et al created a tDCS protocol combined with computerized cognitive rehabilitation for PD patients with improvement in cognitive functions (language, attention, and executive) [ 55 ].…”
Section: Methodsmentioning
confidence: 99%